Synthesis of four series of quinoline‐based heterocycles by reacting 2‐chloroquinoline‐3‐carbonitriles with various types of isocyanides. (10th June 2019) - Tanbakouchian, Zahra; Zolfigol, Mohammad Ali; Notash, Behrouz; Ranjbar, Maryam; Shiri, Morteza
Abstract : Four distinct sets of functionalized quinolines were synthesized by reacting 2‐chloroquinoline‐3‐carbonitriles with various types of isocyanides under appropriate conditions. The palladium‐catalysed reaction of less hindered aliphatic and aromatic isocyanides with 2‐chloroquinoline‐3‐carbonitriles yielded 2‐alkyl(aryl)‐1‐imino‐1 H ‐pyrrolo[3, 4‐ b ]quinolin‐3(2 H )‐one derivatives; however, the catalysed reaction of more hindered isocyanides such as tert ‐butyl isocyanide produced the corresponding 3‐cyanoquinoline‐2‐carboxamides. Interestingly, chloroquinoline‐3‐carbonitriles reacted with ethyl isocyanoacetate in the presence of Cs2 CO3 to generate imidazo[1, 5‐ a ]quinoline derivatives; notably, tosylmethyl isocyanide under the same conditions formed unprecedented 2‐tosyl‐3‐cyanoquinolines. Abstract : The palladium‐catalysed reaction of isocyanides with 2‐chloroquinoline‐3‐carbonitriles yielded 2‐alkyl(aryl)‐1‐imino‐1 H ‐pyrrolo[3, 4‐ b ]quinolin‐3(2 H )‐ones and 3‐cyanoquinoline‐2‐carboxamides. Interestingly, chloroquinoline‐3‐carbonitriles reacted with ethyl isocyanoacetate in the presence of Cs2 CO3 to generate imidazo[1, 5‐ a ]quinoline derivatives; notably, tosylmethyl isocyanide under the same conditions formed unprecedented 2‐tosyl‐3‐cyanoquinolines.